ANALYSE PHYSICO-CHIMIQUE DES EAUX DE LA RIVIERE TSHOPO ET SON IMPACT SUR LA VIE DES ETRES VIVANTS DANS LA VILLE DE KISANGANI - SINGA, Nathan IUNGBI; Fabrice WEMBO MENDO,; Serginho BISELENGE NSAMBI,; Amos IUNGBI SINGA, (IJRDO-Journal of Applied Science, 2019)
The present research focuses on "physico-chemical analysis of the waters of the Tshopo River and its impact on the lives of living beings in the city of Kisangani"The Physico-chemical analysis proves that the pH of the medium is a little basic, that is to say 7.35, the temperature varies from 20 to 25 ° C and its coloration is 53 units of Jackson. The chlorine content is 0%, which allows the arrival of several microorganisms capable of facilitating the pollution of these waters. The waters of the Tshopo River are conducive to living beings from the point of view of conductivity since 0.590 were found against 4 recommended Jackson units. The chemical oxygen demand in its waters is 0.37 mg / l. The chemical analysis of the few measured ions proves that there is: 0.06 mg / l of iron; 24.05 mg / l Calcium; 8.51 mg / l Mg; 0.44 mg / l Nitrite; 0.59 mg / l of nitrate; the Hydroxymetric titre is 32.56 mg / l TH; Turbidity is 58.